The Influence of Job Satisfaction and Transformational Leadership on Organizational Citizenship Behavior with Job Loyalty as a Mediating Variable - Praditya, Rayyan Aqila (Journal of Industrial Engineering & Management Research, 2023)
The purpose of this research is to find 1) the effect of job satisfaction on work loyalty, 2) the effect of transformational leadership on work loyalty, 3) the effect of job satisfaction on organizational citizenship behavior, 4) the effect of transformational leadership on organizational citizenship behavior, and 5) the effect of satisfaction work and transformational leadership on organizational citizenship behavior which is mediated by work loyalty. This research took as its object the Directorate General of Postal and Information Resources and Equipment with a total of 435 employees as respondents. The research method used was taking samples randomly using the sampling method. Keywords: Job Satisfaction, Transformational Leadership, OCB, Job Loyalty.